The FAO Multilateral System for Plant Genetic Resources for Food and Agriculture: Better than Bilateralism? - Muriel Lightbourne (Washington University Journal of Law & Policy, 2009)
Because innovation cycles in the plant breeding industry require five to fifteen years to create new stable varieties, the Multilateral System will not start producing effects for a few more years. However, the share of benefits derived from the commercialization of plant genetic resources that incorporate genetic material accessed from the Multilateral System should be fairly limited pursuant to the provisions of the Standard Material Transfer Agreement adopted by the International Treaty Governing Body in June 2006. This seems to vindicate the position of China and Ethiopia, which consisted of maintaining soybean and coffee outside the Multilateral System. Part I of this Article will show that such is not the case. Part II will then focus on the nature of the SMTA and compare its features to those of the GNU General Public License, with a particular focus on materials under development and benefit-sharing provisions. This Article suggests that, in order to avoid hold-up situations further down the road in the innovation process and high transaction costs, materials developed by public international research centers should not be protected by intellectual property rights, whose impact on the implementation of the International Treaty is analyzed in Part III. It concludes that the International Treaty is better than its alternative, i.e., a cluster of bilateral agreements.
Keywords: Germplasm resources; Plants; International cooperation; Intellectual property; Food & amp; Agriculture Organization of the United Nations; Multilateralism; Plant genetic engineering; Plant genetics; Convention on Biological Diversity; International Treaty on Plant Genetic Resources for Food and Agriculture; 2001; International